2021
DOI: 10.3389/fcell.2021.699554
|View full text |Cite
|
Sign up to set email alerts
|

The Action of Reproductive Fluids and Contained Steroids, Prostaglandins, and Zn2+ on CatSper Ca2+ Channels in Human Sperm

Abstract: The sperm-specific Ca2+ channel CatSper registers chemical cues that assist human sperm to fertilize the egg. Prime examples are progesterone and prostaglandin E1 that activate CatSper without involving classical nuclear and G protein-coupled receptors, respectively. Here, we study the action of seminal and follicular fluid as well of the contained individual prostaglandins and steroids on the intracellular Ca2+ concentration of sperm from donors and CATSPER2-deficient patients that lack functional CatSper cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 82 publications
(149 reference statements)
11
19
0
Order By: Relevance
“…The endogenous steroid hormones testosterone and 17 β -estradiol ( 36 and 37 ) had moderate potency for eliciting sperm calcium uptake, consistent with previous reports ( Blackmore et al, 1990 ; Brenker et al, 2018b ; Rehfeld et al, 2020 ; Jeschke et al, 2021 ), but contrasting with another study that found no CatSper activation by these steroids ( Mannowetz et al, 2017 ). Given the activity of testosterone, 11 β -methyl-19-nortestosterone (11 β -MNT, 38 ) and 7 α -methyl-19-nortestosterone (7 α -MNT, 39 ) were tested.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…The endogenous steroid hormones testosterone and 17 β -estradiol ( 36 and 37 ) had moderate potency for eliciting sperm calcium uptake, consistent with previous reports ( Blackmore et al, 1990 ; Brenker et al, 2018b ; Rehfeld et al, 2020 ; Jeschke et al, 2021 ), but contrasting with another study that found no CatSper activation by these steroids ( Mannowetz et al, 2017 ). Given the activity of testosterone, 11 β -methyl-19-nortestosterone (11 β -MNT, 38 ) and 7 α -methyl-19-nortestosterone (7 α -MNT, 39 ) were tested.…”
Section: Resultssupporting
confidence: 87%
“…The observed steroid SAR, including the low activity of steroids with modified D rings, is consistent with previous studies of steroid-induced calcium influx ( Blackmore et al, 1990 ; Jeschke et al, 2021 ). Interestingly, several steroid activators were shown to activate CatSper by binding to the same site ( Jeschke et al, 2021 ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…PGs such as PGE1 potentiates CatSper at the low concentrations through binding sites other than that of progesterone and how the combined action of progesterone and PGs influences sperm function remains to be established [47,94,95]. In mammalian system, PGE2-EP2 signaling activates chemokines CCL-7 signaling which facilitates sperm migration to the cumulus egg complex and integrin-mediated cumulus extracellular matrix (ECM) assembly helps sperm to penetrate the oocyte [85].…”
Section: Pg Signaling Pathwaysmentioning
confidence: 99%